Antibody-Functionalized MoS2 Nanosheets for Targeted Photothermal Therapy of Staphylococcus aureus Focal Infection - Zhang, Yuqian; Xiu, Weijun; Gan, Siyu; Shan, Jingyang; Ren, Shaokang; Yuwen, Lihui; Weng, Lixing; Teng, Zhaogang; Wang, Lianhui (Frontiers in Bioengineering and Biotechnology, 2019)
Bacterial biofilm-related diseases cause serious hazard to public health and bring great challenge to the traditional antibiotic treatment. Photothermal therapy (PTT) has been recognized as a promising alternative solution. However, the therapeutic efficacy of PTT is often compromised by the collateral damage to normal tissues due to the lack of bacteria-targeting capability. Here, a Staphylococcus aureus (S. aureus)-targeted PTT nanoagent is prepared based on antibody (anti-protein A IgG), polydopamine (PDA), and PEG-SH (thiol-polyethylene glycol) functionalized MoS2 nanosheets (MoS2@PDA-PEG/IgG NSs, MPPI NSs). The PDA was used as bio-nano interface to facilitate the covalent conjugation of antibody and PEG-SH onto the surface of MoS2 NSs via facile catechol chemistry. Targeted PTT of MPPI NSs shows excellent inactivation efficiency of larger than 4 log (>99.99%) to S. aureus both in biofilms in vitro and in infected tissues in vivo without causing damage to normal mammalian cells. By contrast, non-targeted PTT of MoS2@PDA-PEG NSs (MPP NSs) only kills S. aureus by <90% in vitro and <50% in vivo. As a result, S. aureus focal infection in mice healed much faster after PTT of MPPI NSs than that of MPP NSs. The superiority of targeted PTT may originate from the efficient accumulation and close binding of PTT agents to bacterial cells. Therefore, MPPI NSs with bacteria-targeting capability are promising photothermal agents for effective treatment of S. aureus focal infection.